Identification of epigenetically regulated genes distinguishing intracranial from extracranial melanoma metastases - Westphal, Dana; Meinhardt, Matthias; Grützmann, Konrad; Schöne, Lisa; Steininger, Julian; Neuhaus, Lena T.; Wiegel, Miriam; Schrimpf, Daniel; Aust, Daniela E.; Schröck, Evelin; Baretton, Gustavo B.; Beissert, Stefan; et al. (The journal of investigative dermatology, 2023)
Despite remarkable advances in treating patients with metastatic melanoma, the management of melanoma brain metastases remains challenging. Recent evidence suggests that epigenetic reprogramming is an important mechanism for the adaptation of melanoma cells to the brain environment. In this study, the methylomes and transcriptomes of a cohort of matched melanoma metastases were evaluated by integrated omics data analysis. The identified 38 candidate genes displayed distinct promoter methylation and corresponding gene expression changes in intracranial compared with extracranial metastases. The 11 most promising genes were validated on protein level in both tumor and surrounding normal tissue using immunohistochemistry. In accordance with the underlying promoter methylation and gene expression changes, a significantly different protein expression was confirmed for STK10, PDXK, WDR24, CSSP1, NMB, RASL11B, phosphorylated PRKCZ, PRKCZ, and phosphorylated GRB10 in the intracranial metastases. The observed changes imply a distinct intracranial phenotype with increased protein kinase B phosphorylation and a higher frequency of proliferating cells. Knockdown of PRKCZ or GRB10 altered the expression of phosphorylated protein kinase B and decreased the viability of a brain-specific melanoma cell line. In summary, epigenetically regulated cancer-relevant alterations were identified that provide insights into the molecular mechanisms that discriminate brain metastases from other organ metastases, which could be exploited by targeting the affected signaling pathways.